TAKING MEASURES TO ENSURE THE SAFETY OF PEDESTRIAN TRAFFIC AROUND THE SHOPPING MARKETS LOCATED IN THE CITY OF NAMANGAN. (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article presents an analysis and recommendations for improvingthe safety of road users at pedestrian crossings.